What can Africa contribute to global meat demand? Opportunities and constraints - Rich, Karl M. (SAGE Publications, 2009)
While Africa has traditionally been constrained in world markets by low productivity, animal diseases and high standards for animal health and food safety, the growing demand for meat and the emergence of alternative policy mechanisms for facilitating exports could increase Africa's importance as a global supplier of livestock products. This paper outlines Africa's current role in global meat markets and highlights constraints and opportunities. A key constraint that militates against large-scale exports from Africa is its lack of competitiveness vis-à-vis competitors such as Brazil and India. Africa will need to invest in market development, productivity measures, feed resources and infrastructure to reduce production costs and facilitate effective marketing efforts.